A Higher Cardiothoracic Ratio Is Associated with 2-Year Mortality after Hemodialysis Initiation - Ito, Kiyonori (Nephron Extra, 2015)
A high cardiothoracic ratio (CTR) is indicative of a cardiac disorder. However, few reports have revealed an association between the CTR and mortality in patients starting hemodialysis (HD). METHODS: Patients with HD initiation (n = 387; mean age, 66.7 ± 12.7 years) were divided into the following three groups according to their CTR at HD initiation: CTR <50%, 50% ≤ CTR < 55%, and CTR ≥55%. Kaplan-Meier analysis was performed to compare 2-year all-cause mortality among these groups. Furthermore, we investigated the factors affecting their 2-year mortality using a Cox proportional hazard regression analysis. RESULTS: Sixty-five patients (17%) died within 2 years after HD initiation. Kaplan-Meier analysis showed that patients with CTR ≥55% had a higher mortality rate than those in the other groups. Cox proportional hazard regression analysis was performed using parameters with p values <0.1 among these three groups [sex, age, presence or absence of ischemic heart disease, hemoglobin levels, serum albumin levels, CTR, body mass index (BMI)] and confounding factors [presence or absence of diabetes mellitus, and estimated glomerular filtration rate (eGFR)]. Age, eGFR, BMI, and CTR ≥55% at HD initiation were identified as factors influencing 2-year mortality. CONCLUSION: CTR >55% is one of the most important independent factors to affect 2-year all-cause mortality. Thus, confirming the cardiac condition of patients at HD initiation with a CTR >55% may improve their survival.